A Single-Dose, Open-Label Study of the Pharmacokinetics, Safety, and Tolerability of Lisdexamfetamine Dimesylate in Individuals With Normal and Impaired Renal Function. Issue 4 (August 2016) - Ermer, James; Corcoran, Mary; Lasseter, Kenneth; Marbury, Thomas; Yan, Brian; Martin, Patrick T.
Abstract : Background: Lisdexamfetamine (LDX) and D-amphetamine pharmacokinetics were assessed in individuals with normal and impaired renal function after a single LDX dose; LDX and D-amphetamine dialyzability was also examined. Methods: Adults (N = 40; 8/group) were enrolled in 1 of 5 renal function groups [normal function, mild impairment, moderate impairment, severe impairment/end-stage renal disease (ESRD) not requiring hemodialysis, and ESRD requiring hemodialysis] as estimated by glomerular filtration rate (GFR). Participants with normal and mild to severe renal impairment received 30 mg LDX; blood samples were collected predose and serially for 96 hours. Participants with ESRD requiring hemodialysis received 30 mg LDX predialysis and postdialysis separated by a washout period of 7–14 days. Predialysis blood samples were collected predose, serially for 72 hours, and from the dialyzer during hemodialysis; postdialysis blood samples were collected predose and serially for 48 hours. Pharmacokinetic end points included maximum plasma concentration (Cmax ) and area under the plasma concentration versus time curve from time 0 to infinity (AUC0–∞ ) or to last assessment (AUClast ). Results: Mean LDX Cmax, AUClast, and AUC0–∞ in participants with mild to severe renal impairment did not differ from those with normal renal function; participants with ESRD had higher mean Cmax and AUClast than those with normal renal function. D-amphetamine exposure (AUClast and AUC0–∞ ) increased and Cmax decreased as renal impairment increased. Almost no LDX and little D-amphetamine were recovered in the dialyzate. Conclusions: There seems to be prolonged D-amphetamine exposure after 30 mg LDX as renal impairment increases. In individuals with severe renal impairment (GFR: 15 ⩽ 30 mL·min −1 ·1.73 m −2 ), the maximum LDX dose is 50 mg/d; in patients with ESRD (GFR: <15 mL·min −1 ·1.73 m −2 ), the maximum LDX dose is 30 mg/d. Neither LDX nor D-amphetamine is dialyzable. Abstract : Supplemental Digital Content is Available in the Text.